The predictive value of echocardiographic parameters regarding appearance of atrial fibrillation in patients with acute coronary syndrome - V.Y. Tseluyko; F. Ben Salem; N.A. Lopina (Кардіохірургія та інтервенційна кардіологія)
The aim – to determine the predictive value of echocardiographic indicators for the risk of atrial fibrillation (AF) in patients with acute coronary syndrome (ACS) during the hospital period. Materials and methods. 125 patients hospitalized with ACS at the center of percutaneous coronary interventions during four years (2015-2018) were examined; 65 of them had AF. The criterion for inclusion in the study was the presence of ACS; exclusion criteria were the presence of severe concomitant diseases (active oncological processes, chronic renal failure, etc.), heart disease, refusal of the patient to participate in the study. The patients were divided into groups according to the presence of AF. Group 1 included patients with AF. Those of them who had the new-onset AF during ACS hospitalization constituted subgroup 1a (n = 41). Patients in whom AF was observed prior to the development of ACS composed subgroup 1b (n = 24). Group 2 included patients without AF earlier and during hospitalization (n = 60). Results. Patients with AF of the 1st group had a significantly larger left atrium as compared to patients of the 2nd group (p1-2 = 0.002). Among patients with AF, complicating the course of ACS, Killip class I of acute heart failure was more likely to be recorded in ACS than in patients of group 2 (p = 0.05) with less left atrial size compared to patients with AF known before ACS (p1a-1b = 0.005). The patients of the 1st group and the 1a subgroup had significantly lower values ​​of ejection fraction compared to patients of the 2nd group (p1-2 = 0.00039, p1a-2 = 0.00035). In the 1a-subgroup, mitral regurgitation was more significant (p1a-2 = 0.008). Mean pulmonary artery pressure was significantly higher in patients of the 1st group and 1a subgroup than in the 2nd group (p1-2 = 0.0005, p1a-2 = 0.013). Direct correlations were established between mean pulmonary artery pressure and CPK-MB levels (R=0.65; p=0.04), as well as NT-proBNP (R = 0.70; p = 0.004) in patients with AF complicating ACS. Conclusions. Left ventricular ejection fraction has a predictive value for estimating risk of new-onset AF in patients with ACS, with distribution point 50%. The pulmonary artery mean pressure also has a predictive value , with distribution point 35 mm Hg.